The Challenges of Developing Islamic Education Curriculum and Strategies for Its Development in Facing Future Competency Demands - Zainuddin; Amrullah, Abdul Malik Karim; Zuhriyah, Indah Aminatuz (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The development of the Islamic education curriculum encounters various complex challenges stemming from both internal and external factors. Key challenges include the dynamics of globalization, socio-cultural changes, technological advancements, and the need to balance religious values with 21st-century competencies. This study examines these challenges, focusing on issues such as rapid technological progress, the integration of global and local values, and strategies for developing a curriculum that is relevant, flexible, and aligned with modern educational goals. Employing a qualitative approach, the research utilizes literature reviews and expert interviews to analyze the dynamics of curriculum development in Islamic education. The findings reveal that the challenges faced by Islamic education significantly impact both its internal and external dimensions. Internal challenges include achieving the eight national education standards, addressing the demographic bonus resulting from Indonesia's population growth, and tackling character development issues. To remain competitive in the era of globalization and produce graduates who meet contemporary demands, Islamic education must focus on developing human resources capable of adapting to current and future needs. On the other hand, external challenges are more forward-looking, requiring Islamic education to prepare for future demands related to social issues, advancements in technology and information, the growth of creative and cultural industries, and the internationalization of education, including the pursuit of world-class university standards.